2005
DOI: 10.1161/01.hyp.0000174617.09146.d4
|View full text |Cite
|
Sign up to set email alerts
|

Arterial Compression of the Retro-Olivary Sulcus of the Ventrolateral Medulla in Essential Hypertension and Diabetes

Abstract: Abstract-Pulsatile arterial compression in the retro-olivary sulcus along the surface of the ventrolateral medulla has been postulated as a mechanism in both essential hypertension and diabetes. The objective of this study was to test the independent effect of arterial compression in the retro-olivary sulcus on each of these diseases, using separate logistic regression models to control for other known risk factors. Study design was case-control. The study population consisted of 147 consecutive patients treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…Furthermore, two other studies using MR imaging techniques also demonstrated a significant association between compression of the vertebral artery and changes in the posterior fossa of hypertensive but not normotensive individuals. 9,10 Thus, alterations in Atlas anatomy can generate changes in the vertebral circulation that may be associated with elevated levels of BP.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, two other studies using MR imaging techniques also demonstrated a significant association between compression of the vertebral artery and changes in the posterior fossa of hypertensive but not normotensive individuals. 9,10 Thus, alterations in Atlas anatomy can generate changes in the vertebral circulation that may be associated with elevated levels of BP.…”
Section: Introductionmentioning
confidence: 99%
“…The first, posterior fossa decompression of the left RVLM utilising microscopy and also endoscopy has shown some sustained benefit in small case series and has been vindicated to some extent by MRA findings of perimesencephalic vascular compression as a risk factor for hypertension [74]. However, further controlled studies in larger samples of patients are required to confirm its benefit, and its extension to the amelioration of acquired diabetes mellitus appears questionable and less robustly supported by radiological evidence [74, 75]. …”
Section: Discussionmentioning
confidence: 99%
“…[911] The question of whether arterial compression acted as an independent predictor of essential hypertension (apart from other known risk factors) was addressed in larger multivariable retrospective designs. [28] In a case-control study of 147 patients, it was found that the odds of arterial compression among hypertensive subjects were 2.99 times the odds among normotensive subjects ( P = .04), controlling for hypertension risk factors such as age, body mass index, race, diabetes and family history of hypertension. Of compressed hypertensive subjects, 56% were compressed on the left and 44% on the right.…”
mentioning
confidence: 99%
“…Of compressed hypertensive subjects, 56% were compressed on the left and 44% on the right. [8] Collectively, these studies are building a body of evidence to aid the selection of patients eligible for microvascular decompression, i.e., those with intractable hypertension, elevated sympathetic tone, and arterial compression in accordance with a refined map of the human ventrolateral medullary surface and its relationship to cardiovascular control.…”
mentioning
confidence: 99%